ANALISIS KADAR LOGAM MERKURI DALAM KOSMETIK MENGGUNAKAN METODE SPEKTROSKOPI SERAPAN ATOM (SSA) - Ayu Ningrum, Jannati; Rosa Fane, Elvira; Andhini, Nina (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the levels of mercury metal in the Specified samples to determine the level of contamination and potential Risks to the environment and human health. Mercury is a very toxic heavy metal and can cause serious damage to the nervous system, kidneys, and other Organs. The analytical method used in this study is atomic absorption Spectrophotometry (AAS), which has high sensitivity and accuracy in detecting mercury even in small concentrations. Therefore, it is necessary to test the levels of mercury heavy metals by BPOM regulation no.3 of 2022 which prohibits the mixing of mercury heavy metals in cosmetics. After the analysis was carried out, all samples 1(1) as much as 136.82 ppb, cosmetics 1(2) much as 40.804 ppb ppb, cosmetics 2(1) as much as 155.40 ppb, and cosmetics 2(2) as much as 70.23 ppb. Where this does not meet the maximum Requirements for heavy metal content based on BPOM regulation Number 3 of 2022.